Rice grassy stunt virus-free and pathogenic rice plants affect the brown planthopper (Nilaparvata lugens Stål) life cycle - Na Phatthalung, Thanat; Tangkananond, Wipa (Agriculture and Natural Resources, 2021)
RESOURCESThe developmental duration and performance of the brown planthopper (BPH, Nilaparvata lugens Stål), which is an important insect vector, can be influenced by transmission of Rice grassy stunt virus (RGSV) in irrigated rice cultivation in Asian countries including Thailand. In this study, the interaction effect between the statuses (non-viruliferous and viruliferous) of BPH populations on free leaves and RGSV-diseased leaves were investigated using a 2 × 2 factorial in CRD with five replications. The results indicated that there were no significant (p > 0.05) interaction between the statuses of BPH vectors and rice plants. In addition, the effects of different RGSV-inoculation periods (10, 20, 30, 40, 50, 60, 70, 80 and 90 days after inoculation) on the developmental periods of each life cycle stage of the non-viruliferous BPH population were investigated following CRD with five replications. The different inoculation periods of rice significantly affected (p < 0.05) developmental periods of the first and fourth instar nymph stages as well as on survival periods of both male and female short-winged brachypterous form and long-winged macropterous form. On the contrary RGSV-inoculation periods did not affect (p > 0.05) developmental periods of the eggs and other instar stages. These results can be used to improve the effectiveness of insect and rice viral disease control policies and strategies; epidemiological modelling of the virus and vector; outbreak prediction and protection; and agro-ecosystem management systems.